(untitled) (Eurasian Research Bulletin, 2023)
Study aims to use a McCarthy model as a modern and advanced model of one of the teaching methods used in teaching some movements in the ground gymnasium, including the frontal leap on the rug of the ground movements of the juniors, and the researcher used the experimental curriculum in the manner of the first and second Terbette groups. The juniors (10) years of mascara, where the educational and training curriculum was implemented and applied to the two experimental groups for a period of (12) weeks for each group on for a period of 12 weeks. (Educational units per week and the duration of each educational unit (90) minutes